Symbolic-Fiscal Hermeneutics: Reframing the APA Model in Indonesia from Post-Hegelian Dialectics to Ricoeurian Ethics (2004–2025) - Apollo (Green Publisher, 2025)
This article examines the evolution of the Attributional–Predictive–Accounting (APA) model within the Indonesian Stock Exchange (IDX) from 2004 to 2025. Drawing from a combination of Post-Hegelian Left critique (Marx, Adorno, Marcuse) and Ricoeurian hermeneutics, it argues that fiscal instruments such as audit reports, financial statements, and tax policies are not merely technical or empirical outputs, but deeply symbolic texts that encode ideological meaning, ethical framing, and political intent. The study introduces a new theoretical synthesis Symbolic-Fiscal Hermeneutics to interpret how accounting practices shape, and are shaped by, historical discourse, institutional power, and the ethics of transparency and redemption. Using a qualitative interpretive-genealogical method, the study triangulates over 100 fiscal documents, including regulatory policies, corporate financial reports, and government-issued tax circulars across three distinct political periods. Through Ricoeur’s threefold mimesis and critical dialectics, the research traces the shifting symbolic grammar of APA: from rational-managerial causality during the technocratic Yudhoyono era, to moralized fiscal forgiveness in the 2016 and 2022 tax amnesties under President Jokowi, and ultimately to algorithmic prediction and depersonalized reporting in the post-pandemic digital audit regime. The fiscal subject emerges not as a stable actor, but as a dynamic construct mediated by narrative, risk discourse, and symbolic legitimacy. Findings demonstrate that APA-based accounting is performative: it configures fiscal identity, produces institutional memory, and reproduces governance ideologies through the aesthetic of numbers and the ethics of disclosure. The study urges a rethinking of accounting not as a neutral function, but as a narrative-ethical practice. By reading fiscal texts as sites of symbolic struggle, the article contributes a new lens for critical accounting research and fiscal philosophy in emerging economies. This study introduces Symbolic-Fiscal Hermeneutics as a new theoretical framework that fuses Post-Hegelian critique with Ricoeurian hermeneutics to analyze accounting not as measurement, but as symbolic narration that shapes fiscal subjectivity and ethical governance in transitional economies.